Learning in Synchrony with the Life - Abarca-Alpízar, Flor (2017)
As humanity, we suffer the disconnection and separation from life as a whole. This rupture, imposed by the predominant systematic paradigm during the last four hundred years, has led us to forget the holistic vision preserved by ancient cultures. This situation is also prevalent in our educational systems, controlled by the rote fragmented education, which is distant from life and from the existence and feelings of those who are learning. To overcome the current planetary crisis, it is urgent to recover the holistic vision of both life and learner, where the educational university processes are essential components for the development of professionals committed with the plenitude of life on earth. The essence of this essay is to reflect about the importance that has, for the improvement of the current planetary crisis, the recovery of our connectivity with life on earth, synchronized with the learning processes, because learning processes and vital processes mean the same thing. This essay is divided in three moments. The first one originates from the exchange of beings, knowledge, feelings and experiences, to recover our lost connection with life on earth. The second moment starts with the introduction of reflections and conceptualizations, by means of the collective construction of knowledge, with the support of specialists in the holistic vision and the processes of peer-learning, which are so necessary to save life as a whole. The third moment of this essay is explained with proposals, key ideas, symbols and signs for the connection of the vital processes, in sync with the necessary learning processes in the current times.